Analisis Deskriptif Kemampuan Menulis Teks Narasi Siswa Kelas VIII SMP Negeri 1 Gunungsitoli Barat Tahun 2020/2021 - Hasrat Sozanolo Harefa; Joshua Obedience Zebua (INTELEKTIUM, 2021)
Writing is one of the four language skills that should be mastered by students. The syllabus of SMP Negeri 1 Gunungsitoli Barat expects the students to be able to compiling the narrative text in the form of personal experience. The purpose of the research was describing the students’ writing ability in narrative text and the factors affecting it. The method used in the research was descriptive qualitative. The analysis of the data was conducted by following steps. Analyzing the quantitative data by using analytic scoring rubric from Glenceo namely, focus/organization, elaboration/support/style, and grammar and mechanics and analyzing the qualitative data through transcripts of structure interviews. Furthermore, the informant of the research was class VIII-A students of SMP Negeri 1 Gunungsitoli Barat which consisted of 20 students. The data were collected through documentary data of students’ worksheets and interview both students and English teacher. The result showed that the students’ ability in writing narrative text was in Good category (66 score). It is proved by the findings that there were 7 students (35%) included in ‘Excellent’ category, there were 4 students (20%) included ‘Good category, there were 3 students (15%) included ‘Fairy’ category and category included in ‘Poor’ were 6 students (30%). Furthermore, the factors that affect the students’ ability in writing narrative text were: students cognitive it was problem organization, less motivation, lack of grammar, lack of practice and the influence of the first language (L1) on writing in English.